All-cause hospital admissions and incidence of asthma in children in Kazakhstan: a population-based retrospective cohort study - Dmitriy Syssoyev; Kamilla Mussina; Dimitri Poddighe; Abduzhappar Gaipov; Dinara Galiyeva (Scientific Reports)
Abstract This study describes the incidence of asthma and all-cause hospital admissions among children in Kazakhstan diagnosed between 2014 and 2021. In this retrospective cohort study, we included children aged 0–17 years diagnosed with asthma (ICD-10 codes J45.x) and registered in the Unified National Electronic Health System (UNEHS) during 2014–2021. In the outpatient asthma subgroup, we analyzed asthma incidence rates per 100,000 population and all-cause hospitalization rates per 1,000 person-years. Cox regression was used to assess hospitalization risks. The cohort included 53,463 children, 63.7% male, 47.9% aged 5–11 years, and 74.1% urban residents. The incidence rate ranged from 67.5 to 185.9 among boys and 38.2 to 115.7 among girls per 100,000 population, highest in the 5–11 age group (308–351 cases). Among 31,525 outpatients, 915 (2.8%) were hospitalized, with an incidence rate of 6.91 per 1,000 person-years. The 5–11 age group had a 2.59 times higher hospitalization risk than the 0–4 age group. Respiratory infections, allergic rhinitis, and acute rhinosinusitis were the factors associated with the highest risks of hospitalization (HRs: 14.48, 12.95, and 7.28, respectively). The insights from this study enhance our understanding of asthma in Kazakhstan and offer valuable lessons applicable to similar contexts globally.